Dehydrated Cranberry Juice Powder Obtained by Osmotic Distillation Combined with Freeze-Drying: Process Intensification and Energy Reduction - Reyes-Salinas, A; Zuniga-Navarro, G; Romero-Figueroa, J; Merlet-Venturelli, G; Cabezas-Cornejo, R (Institution of Chemical Engineers, 2020)
The aim of this work was the study of the energy efficiency of the dehydration process of cranberry juice using osmotic distillation (OD) in combination with freeze-drying. To achieve this process, OD was performed on a hollow fiber membrane contactor with an initial sugar content of 8°Brix in the cranberry juice. This solution was concentrated to four different final concentrations (25, 35, 45 and 57°Brix) with the purpose of reducing the lyophilization time obtaining a 100% dried product, using as a response variable the processing time. From these obtained results, and when comparing the 8°Brix juice lyophilization to the process achieved by the combination of OD and freeze-drying, a decrease in the total process time could not be achieved for any experimental assay. However, the 57°Brix cranberry juice previously concentrated by OD presented an 86% decrease in the energy requirements to obtain the same dehydrated product. Finally, a reduction of the energy consumption for all the experimental runs was observed in the samples concentrated by OD, as the step previous to lyophilization, achieving an intensification in the efficient energy use during this process, maintaining the same characteristics of the final product. © 2020 Institution of Chemical Engineers